High cultures and low cultures displayed: the metamorphosis of the “Sacro Catino” of Genoa between chivalrous themes and foundation myths - Molteni, Ilaria (Eikón / Imago, 2022)
The “Sacro Catino”, an exotic object that arrived in Genoa around 1100, receives various identifications between the 12th and 13th centuries: from a marvelous artefact to the Holy Grail, a relic of the Passion. Analyzing the identifications of the basin in the light of the dialogue with the literary world, this essay investigates the transformation of exclusive and complex themes into elements of the city's memory. The article first focuses on the appropriation of the Grail motif, and shows how the visual treatment that the theme receives in Arthurian novels makes this literature the ideal vehicle for identifying the basin with the Grail and thus displaying Eucharistic dogmas and mysteries. The second part examines the place where the Basin-Graal association is established, the Chronicle of the Archbishop of Genoa Jacopo da Varagine, and describes how this work is at the origin of the construction of a monumental scenography dedicated to the foundation myths Genoese which finds its place in the cathedral and in which the basin also participates. The basin is therefore involved in a relationship of circularity between literature traditionally intended for a few and the monumentalization of literary themes and at the same time it is a visual and tangible testimony of strategies that exploit the gradation of high and low cultural plans for the construction of collective memory.